2017
DOI: 10.1002/ajmg.a.38305
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric charts and congenital anomalies in newborns with Down syndrome

Abstract: The objectives of this study were to obtain updated neonatal measurements in French newborns with Down Syndrome (DS) according to their gestational age, and to assess the frequency and distribution of congenital anomalies. Data on congenital malformations, birth weight, birth length and birth occipito-frontal circumference (OFC) according to the gestational age was gathered from 1,030 babies, born between 1980 and 2010. The mean gestational age was 38 weeks from the date of the last menstrual period (LMP) (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
5
1
2
Order By: Relevance
“…In our previous study, we found no difference between Toledo's study and ours for birth OFC measurement for boys and girls (Mircher et al, ). When we compared OFC at age 14, we found no difference between Toledo's study and ours for boys, whereas our girls' OFC was slightly bigger, but we miss data to perform statistical comparisons.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In our previous study, we found no difference between Toledo's study and ours for birth OFC measurement for boys and girls (Mircher et al, ). When we compared OFC at age 14, we found no difference between Toledo's study and ours for boys, whereas our girls' OFC was slightly bigger, but we miss data to perform statistical comparisons.…”
Section: Discussioncontrasting
confidence: 63%
“…Therefore, there seems to be two slowdown periods in OFC growth: just before full term (Mircher et al, ) and around 12 months. Several authors have also observed a slowdown between age 0 and 4 (Myrelid et al, ), but some of them earlier than us, around 6 months (Palmer et al, ; Tuysuz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean birth weight and birth length is reduced in new-borns with DS, with mean birth weight closer to the mean of unaffected children than birth length (6). Reduced growth rate leading to short stature in adult age is a well-known characteristic of most persons with DS.…”
Section: Nutritional Statusmentioning
confidence: 99%
“…Growth charts for persons with DS from birth to 18 or 20 years of age have been developed based on several national cohorts (40)(41)(42)(43)(44)(45)(46). Traditionally growth curves may be useful in children to monitor growth and nutritional status.…”
Section: Nutritional Statusmentioning
confidence: 99%
“…El RN con SD también se asocia a un peso de nacimiento inferior al de la población general 28,30,35 . Nuestro 26,4% fue inferior al 30% descrito en otra cohorte chilena y superior a otra con 12% de pacientes con peso menor a 2.000 g y EG promedio de 37,3 semanas 6,13 .…”
Section: Discussionunclassified